Zero-Raum : Leihgabe Koch im Kunstmuseum Düsseldorf. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1973)
Agam, Yaacov ; Arman ; Bury, Pol ; Castellani, Enrico ; Dorazio, Piero ; Fontana, Lucio ; Graubner, Gotthard ; Indiana, Robert ; Klein, Yves ; Mack, Heinz ; Mavignier, Almir ; Megert, Christian ; Oehm, Herbert ; Piene, Otto ; etc.
Zero-Raum : Leihgabe Koch im Kunstmuseum Düsseldorf, 1973
boek